Dual-channel membrane capacitive deionization based on asymmetric ion adsorption for continuous water desalination - Liu, Meijun; Xue, Zhiying; Zhang, Haifeng; Li, Yuna (Electrochemistry communications, 2021)
•Dual-channel MCDI system enable continuous water desalination.•Asymmetric process breaks through the inherent adsorption capacity of electrode.•Different ion diffusion rate results in more than 100% charge efficiency.•RSM was first introduced for optimization of desalination parameters. Capacitive deionization (CDI) systems are well known for their ability to efficiently desalinate water by adsorbing ions onto two electrodes through the application of an electrical potential difference. In this study, we report a continuous desalination device composed of a novel dual-channel CDI cell architecture containing three ion exchange membranes (CAC-MCDI). The adsorption of ions and electrode regeneration from the desorption ions were performed separately in the two channels and enabled continuous water desalination by the application of an intermittent voltage reversal. Additionally, the novel cell architecture performed an electrodialysis-like process when the adsorption of ions on the electrode reached saturation, demonstrating a synergistic effect. For the first time, a CDI system is modified for the asymmetric adsorption of cations and anions, to reveal the effect of the migration rate difference of ions. Fully making use of ion diffusion differences as well as the synergistic effect can effectively improve the performance of the system and surprisingly increase the charge efficiency above 100%. The parameters for the desalination process were first optimized by response surface methodology (RSM), which predicted that the salt removal efficiency and charge efficiency could reach 69.29% and 103.60%, respectively. Both the experimental results and the predicted values from the model indicated that asymmetric ion adsorption capabilities of CAC-MCDI allowed the system to achieve excellent performance and provide continuous water desalination.